Palladium-Catalyzed Decarboxylative [4+2] Cycloaddition of Vinyl Benzoxazinanones with Cyclic N-Sulfimines: Stereoselective Synthesis of Benzosulfamidate-Fused Tetrahydroquinazolines - Mun, Dasom; Kim, Eunjin; Kim, Sung-Gon (Synthesis, 2019)
Methods for the catalytic synthesis of highly functionalized benzosulfamidate-fused tetrahydroquinazolines are presented. The decarboxylative [4+2] cycloaddition of vinyl benzoxazinanones with benzoxathiazine 2,2-dioxides catalyzed by Pd(PPh3)4 affords fused-tetrahydroquinazolines with high diastereoselectivities. Alternatively, catalytic asymmetric [4+2] cycloaddition employing a chiral palladium-containing phosphoramidite ligand provides optically enriched benzosulfamidate-fused tetrahydroquinazolines in good yields and with excellent diastereoselectivities and enantioselectivities.
Keywords: asymmetric catalysis; cycloaddition; vinyl benzoxazinanones; cyclic N-sulfimines; palladium